The Relationship between Depressive Symptoms, Disease State, and Cognition in Amyotrophic Lateral Sclerosis - Jelsone-Swain, Laura M.; Persad, Carol; Votruba, Kristen L.; Weisenbach, Sara L.; Johnson, Timothy D.; Gruis, Kirsten L.; Welsh, Robert C. (Frontiers in Psychology, 2012)
Cognitive impairment (CI) in amyotrophic lateral sclerosis (ALS) may present a serious barrier to a patient’s wellbeing and significantly decrease quality of life. Although reports of cognitive impairment in ALS without frank dementia are becoming quite common, questions remain regarding the specific cognitive domains affected, as well as how other psychological and medical factors may impact cognitive functioning in these patients. Additionally, the influence of depressive symptoms on disease processes is not known. We aimed to address these questions by completing extensive neuropsychological tests with 22 patients with ALS and 17 healthy volunteers. A subgroup of these patients also completed questionnaires to measure depressive and vegetative symptoms. Analyses tested the overall cognitive differences between groups, the influence of physical (e.g. bulbar and limb), vegetative (e.g. fatigue) and depressive symptoms on cognitive performance, and the relationship between depressive symptoms and physical dysfunction in ALS. Overall the patients performed more poorly than healthy controls, most notably on tests of executive functioning and learning and memory. Results suggest that true cognitive performance differences exist between patients with ALS and healthy controls, as these differences were not changed by the presence of vegetative or depressive symptoms. There was no effect of limb or bulbar symptoms on cognitive functioning. Also, patients were not any more depressed than healthy controls, however increased depressive scores correlated with faster disease progression and decreased limb function. Collectively, it is suggested that translational advances in psychological intervention for those with CI and depression become emphasized in future research.